The SUMO ligase MMS21 profoundly influences maize development through its impact on genome activity and stability - Junya Zhang (Public Library of Science (PLoS), 2021)
The post-translational addition of SUMO plays essential roles in numerous eukaryotic processes including cell division, transcription, chromatin organization, DNA repair, and stress defense through its selective conjugation to numerous targets. One prominent plant SUMO ligase is METHYL METHANESULFONATE-SENSITIVE (MMS)-21/HIGH-PLOIDY (HPY)-2/NON-SMC-ELEMENT (NSE)-2, which has been connected genetically to development and endoreduplication. Here, we describe the potential functions of MMS21 through a collection of UniformMu and CRISPR/Cas9 mutants in maize (Zea mays) that display either seed lethality or substantially compromised pollen germination and seed/vegetative development. RNA-seq analyses of leaves, embryos, and endosperm from mms21 plants revealed a substantial dysregulation of the maize transcriptome, including the ectopic expression of seed storage protein mRNAs in leaves and altered accumulation of mRNAs associated with DNA repair and chromatin dynamics. Interaction studies demonstrated that MMS21 associates in the nucleus with the NSE4 and STRUCTURAL MAINTENANCE OF CHROMOSOMES (SMC)-5 components of the chromatin organizer SMC5/6 complex, with in vitro assays confirming that MMS21 will SUMOylate SMC5. Comet assays measuring genome integrity, sensitivity to DNA-damaging agents, and protein versus mRNA abundance comparisons implicated MMS21 in chromatin stability and transcriptional controls on proteome balance. Taken together, we propose that MMS21-directed SUMOylation of the SMC5/6 complex and other targets enables proper gene expression by influencing chromatin structure. Author summary The post-translational addition of SUMO to other proteins by the MMS21 SUMO ligase has been implicated in a plethora of biological processes in plants but the identit(ies) of its targets and the biological consequences of their modification remain poorly resolved. Here, we address this issue by characterizing a collection of maize mms21 mutants using genetic, biochemical, transcriptomic and proteomic approaches. Our results revealed that mms21 mutations substantially compromise pollen germination and seed/vegetative development, dysregulate the maize transcriptome, including the ectopic expression of seed storage protein mRNAs in leaves, increase DNA damage, and alter the proteome/transcriptome balance. Interaction studies showed that MMS21 associates in the nucleus with the NON-SMC-ELEMENT (NSE)-4 and STRUCTURAL MAINTENANCE OF CHROMOSOMES (SMC)-5 components of the chromatin organizer SMC5/6 complex responsible for DNA-damage repair and chromatin accessibility. Our data demonstrate that MMS21 is crucial for plant development likely through its maintenance of DNA repair, balanced transcription, and genome stability.